An approach to the synthesis of the cytochalasans - Harkin, S; Harkin, Shaun Anthony (1983)
﻿ The cytochalasans, a group of biologically active secondary metabolites isolated from micro-organisms, are tricyclic compounds which comprise of a heavily oxygenated 11-, 13- or 14-membered ring trans -fused to a substituted 8-azabicyclo [4.3.0]nonane ring system. One approach to the total synthesis of the cytochalasans involves the intramolecular Diels-Alder cyclization of a suitable 3-substituted- Δ3 - pyrrolin-2-one. As preliminary work, a synthetic route to 5̱S-1-acyl-5- benzyl-3-butyl- Δ3 -pyrrolin-2-ones was developed, starting from the known lactam, 5̱R-5-benzylpyrrolidin-2-one. However, although these dienophiles reacted stereospecifically with 2̱E,4̱E-hexadiene, the reaction conditions were harsh (200°, 30-50 h) and the sequence suffered from low overall yields. The doubly activated dienophile, 5̱S-1-benzoyl-5-benzyl-3-(1-oxopropyl)- Δ3 -pyrrolin-2-one, on the other hand, was available via an expeditious route from the N -protected lactam, 5̱R-5-benzyl-1-(tert-butyldimethylsilyl)pyrrolidin- 2-one. Moreover, the dienophile reacted stereoselectively with 2̱E,4̱Ehexadiene under milder conditions (100°, 8 h) to give, after deprotection, 7-benzyl-2,5-dimethyl-1-(1-oxopropyl)-8-azabicyclo[ 4.3.0] non-3-en-9-one. The stereochemistry of the isoindolone adduct was shown to be the same as in naturally occurring cytochalasans. The overall yield from 5̱R-5-benzylpyrrolidin- 2-one after seven steps was 16%. In comparative studies, the doubly activated dienophile 1-benzenesulphonyl- 3-(1-oxopropyl)- Δ3 -pyrrolin-2-one was prepared and its reactions with 2̱E,4̱E-hexadiene and cyclopentadiene were studied. Although the stereoselectivity was better than for the N-benzoylated pyrrolin-2-one, isolated yields of cycloadducts were inferior. Thus,as a model for ah approach to the [13]cytochalasans, the dienedienophile, 5̱S ,12̱E,14̱E-1-benzoyl-5-benzyl-3-(1-oxohexadeca-12,14-dienyl)- Δ3 -pyrrolin-2-one, was prepared in 20% overall yield from 5̱R-5-benzylpyrrolidin- 2-one. Regio- and stereoselective cyclization was achieved under high pressure conditions (11-13 kbar) to give a tricyclic compound in 16-35% yield. The stereochemistry of the deprotected major adduct was shown to be that required for cytochalasan synthesis. Thus, the intramolecular Diels- Alder approach to cytochalasan synthesis using diene-lactams was validated.